MUATAN SIMBOL VERBAL TIGA BUDAYA INDONESIA DALAM TAYANGAN ’’LAKI-LAKI LASUT’’ DI TRANS TV (PERIODE SEPTEMBER 2011) - Indah Suryawati (Communication, 2012)
The purpose of this study to know the content of verbal symbols of three cultures on impression the ‘’Laki-laki Lasut’’  in Trans TV. The theory used was content analysis. This research method is a method of content analysis with quantitative approach. Research object is the ‘’Laki-laki Lasut’’  in Trans TV, September 2011 period. Sampling technique is random and selected 10 impressions. This type of verbal symbols of culture on impression ‘’Laki-laki Lasut’’, September 2011 period is divided into three categorization, namely the use of language, accent and intonation. The results show that most Balinese culture dominates the ‘’Laki-laki Lasut’’ in Trans TV that is 44.4%. Where the accent is 19%, using the language pronunciation is 14.3% and intonation is 9.7%.